Macromol. Chem. Phys. 18/2017. Issue 18 (September 2017) - Christmann, Julien; Allonas, Xavier; Ley, Christian; Ibrahim, Ahmad; Croutxé‐Barghorn, Céline
Abstract : Back Cover : The photopolymerization ability of a photoinitiating system for free radical polymerization based on isopropylthioxanthone and a triazine derivative is assessed. The prediction ability of a photopolymerization kinetic model is tested taking into account the main reaction steps from the absorption of photons to the formation of the polymer. This is reported by Julien Christmann, Xavier Allonas, * Christian Ley, Ahmad Ibrahim, and Céline Croutxé‐Barghorn in article number1600597 .